Organocatalytic Asymmetric Cascade Reaction of γ‐Substituted Deconjugated Butenolides with o‐Formyl‐β‐nitrostyrene. Issue 28 (26th July 2018) - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal
Abstract: An efficient chemo‐, diastereo‐ and enantio‐selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of β, γ ‐butenolides with o ‐formyl‐ β ‐nitrostyrenes in the presence of bi‐functional hydrogen‐bonding catalyst. Indanol derivatives containing γ, γ ‐disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities. Abstract : Organocatalytic cascade reaction of various γ‐substituted deconjugated butenolides with o ‐formyl‐β‐nitrostyrene to furnish functionally rich chiral indanol dervatives bearing four contiguous stereogenic centers are described.